2014
DOI: 10.1589/jpts.26.1287
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Various Dual Task Training Methods with Gait on the Balance and Gait of Patients with Chronic Stroke

Abstract: [Purpose] This study examined the effects of various dual task gait training methods (motor dual task gait training, cognitive dual task gait training, and motor and cognitive dual task gait training) on the balance and gait abilities of chronic stroke patients. [Subjects and Methods] Thirty-three outpatients performed dual task gait training for 30 minutes per day, three times a week, for eight weeks from June to August, 2012. Balance ability was measured pre-and posttest using the stability test index, the w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 21 publications
0
56
0
3
Order By: Relevance
“…Of the 42 studies, three were RCTs,3436 and 39 were CCTs. Eight studies evaluated the effects of dual-task training on postural stability 3436,48,61–64. Eight studies evaluated the effects of dual tasks on participants suffering from neurological diseases, such as degenerative cerebellar disorder, Parkinson’s disease, and multiple sclerosis 21,65,66.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the 42 studies, three were RCTs,3436 and 39 were CCTs. Eight studies evaluated the effects of dual-task training on postural stability 3436,48,61–64. Eight studies evaluated the effects of dual tasks on participants suffering from neurological diseases, such as degenerative cerebellar disorder, Parkinson’s disease, and multiple sclerosis 21,65,66.…”
Section: Resultsmentioning
confidence: 99%
“…Four studies incorporated only female participants,35,79,85,86 and two studies incorporated only male participants 34,89. Three studies did not specify the gender of the included participants 48,61,80. The included studies provided data on 1,480 participants (n=796 females/581 males).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the elderly population, it has been shown that the inability to perform dual tasks affects gait balance [20], and thus may further increase the risk of falls [19,21,22]. After brain injury, individuals may also be susceptible to this risk since cortical and subcortical areas are required to implement multitasking [23].…”
Section: Discussionmentioning
confidence: 99%
“…In other words, gait training by itself may be beneficial, yet this approach allows the learner to internalize the focus of attention on the movement itself. Dual task training forces an external focus of attention, which has proven to be a superior form of training for stroke and many other impaired and un-impaired (athletics, developmental learning, etc) conditions [75,81,82].…”
Section: Rehabilitation Of Dual Task In Gait…or Rehabilitation Of Gaimentioning
confidence: 99%